The Design and development of model of English training program for local community at rural tourism - Francisca Titing Koerniawaty; Dika Pranadwipa Koeswiryono (Politeknik Negeri Bali, 2017)
The President of Republic of Indonesia issued eight instructions at the Cabinet Forum on January 4th 2016, one if wich was “Ensuring the Development of the 10 National Tourism Destinations or 10 New Bali, to meet the 2019 tourism target, the increasing of national income from 120 billion into 240 billion.Bali as one of Indonesia’s prime tourism destination has also taken participation in increasing the income. This can be seen from the support given by Bali government to establish the development program of ten rural tourism in the program of the development of Bali in tourism for the next four years to develop the rural tourism. Based on this, the research was aimed at participating in the development of Human Resource in areas where rural tourism take place to allow the villagers to interact intensively with foreign tourists and give their best service. The participation was the design and development of English training with syllabus, lesson plan and training material as its results. The training put much emphasis on the increase of English communication ability based on the potential resource of Bedulu Village as one of rural tourism. The method of the research was Design and Development, porposed by Ellis and Levy (2010), that consists of several phases in designing and developing English training. It is expected that the output of the study will results in the realization of society service at rural tourism as English training.